The Relationship between Flexible Work and Job performance among Bank Employees - Ahmad, Nurazwa; Ramlan, Nur Nadia; Shafi, Muhammad Ammar (Research in Management of Technology and Business, 2023)
The banking sector plays an important role in the growth of the Malaysian economy. Employers need to improve the skills, retention and relocation of them to the other roles so that economic growth can grow rapidly. Job performance appraisal for each employee is important because it helps employees achieve personal development and organizational goals while flexible work practices can improve the quality of life of employees and get a lot of response by every employee. The workplace environment that is not suitable for the work to be performed as well as conflicting understanding between employers and employees also affect job performance. This study was conducted to identify the level of work flexibility and job performance and to examine the relationship between flexible work and job performance that focuses on bank employees in Johor. 60 responses were employed in the analyses. The results showed a high level of temporal flexibility and moderate level of spatial flexibility. The job performance among bank empoyees was proven high. The r coefficient value for temporal flexibility and job performance is r = 0.828 while r = 0.590 was found between spatial flexibility and job performance. The correlation is significant at p < 0.01. This finding also indicates a significant model which confirms the existence of the effect between flexible work and job performance. 69.6 percent of the variation in job performance can be explained by flexible work (R2 = 0.696). Therefore, the result suggests that banks take initiatives to improve the job performance of bank employees while taking into consideration on temporal flexibility more than spatial flexibility.